Molecular Targets of β-Lactam-Based Antimicrobials: Beyond the Usual Suspects - Monika I. Konaklieva (MDPI AG, 2014)
The common practice in antibacterial drug development has been to rapidly make an attempt to find ever-more stable and broad-spectrum variants for a particular antibiotic, once a drug resistance for that antibiotic is detected. We are now facing bacterial resistance toward our clinically relevant antibiotics of such a magnitude that the conversation for antimicrobial drug development ought to include effective new antibiotics with alternative mechanisms of action. The electrophilic β-lactam ring is amenable for the inhibition of different enzyme classes by a suitable decoration of the core scaffold. Monocyclic β-lactams lacking an ionizable group at the lactam nitrogen exhibit target preferences toward bacterial enzymes important for resistance and virulence. The present review intends to draw attention to the versatility of the β-lactams as antimicrobials with "unusual" molecular targets.